What it Takes to Lower Regulatory Risk in Infrastructure Industries : An Assessment and Benchmarking of Brazilian Regulators - Correa, Paulo (World Bank, Washington, DC, 2012)
This article points out that regulatory governance-how regulators manage concession contracts, or other public-private contractual arrangements and sector laws-can affect the private sector's perception of regulatory risk and thus the availability of private capital for infrastructure projects. Four key elements of the regulatory governance structure can reduce the risk of regulatory failure: political and financial autonomy, decision-making structures that reduce regulatory discretion, access to effective enforcement and other regulatory tools, and efficient rules of accountability. This note presents an analytical framework based on those four elements and applies it in assessing regulatory governance in Brazil.